PENGARUH HARGA, PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN SEPEDA MOTOR MEREK HONDA DI SAMARINDA TAHUN 2019 - Omar Dhanny; Muhammad Kadafi; Yunandha Siswa (Jurnal Eksis, 2019)
This study aims to determine the effect of price, promotion and product quality on consumer satisfaction of Honda brand motorcycles in Samarinda both partially and simultaneously. This research is a survey research. The population in this study is the people in Samarinda. The sampling technique uses accidental sampling with a total sample of 100 people. Data collection techniques using questionnaires or questionnaires that have been tested for validity and reliability.  The data analysis technique used is multiple linear regression. The results of this study indicate that: (1) the price has a significant effect on the satisfaction of Honda motorcycle consumers, as evidenced by the significance value of 0.002 < 0.05, and (2) the promotion has no significant effect on Honda motorcycle consumer satisfaction, as seen from the significance value 0.161 > 0.05, and (3) product quality has a significant effect on the satisfaction of Honda motorcycle consumers, as evidenced by the significance value of 0,000 < 0,05, and (4) the price, promotion and quality of products have an influence on the satisfaction of Honda motorcycle consumers in Samarinda, evidenced by the results of the test obtained F count value of 29.446 with a significance of 0.000 < 0.05. Keywords: Price, Promotion, Product Quality, and Consumer Satisfaction.